Analisis Break Even Point Multi Produk Sebagai Alat Perencanaan Laba Pada Homestay Ibu Iis Di Situs Wisata Gunung Padang - Sakila, Mutiara; Masodah, Masodah (Sanskara Akuntansi dan Keuangan, 2024)
This research was created to determine and analyze the profit planning of Ibu Iis' Homestay by calculating the break even point. The research subjects were conducted at Ibu Iis Homestay which is located on Kp. Gunung Padang, Karyamukti Village, District. Campaka, Kab, Cianjur West Java Indonesia. Data was obtained directly through interviews by asking questions to Mrs. Iis as the homestay owner. The analytical tools used are Break even point and Margin of safety. The research results show that in 2022 the break even point for multi-room products is 47 outdoor room units and 14 indoor room units. Room rental at the break even point is in Rupiah, namely an outside room of Rp. 4,728,451 and the inner room is Rp. 2,072,535. Minimum room rental for homestays is 97 units and indoor rooms are 29 units. Sales in rupiah for outside rooms are Rp. 9,700,000 and for inner rooms Rp. 4,350,000 . The margin of safety at Mrs. Iis's homestay in 2022 in percentage for outside rooms is IDR. 38.59% and for inside rooms it is 7.98% while in rupiah for outside rooms it is Rp. 2,424,740 and for inner rooms Rp. 724,273. Changes in factors that influence the Break Even Point at Ibu Iis' homestay are changes in room rental prices and variable costs. If the room rental price is increased by 25%, the break even point decreases and profits increase. Likewise, if the rental price is reduced by 10%, the break even point increases and profits decrease. If variable costs are increased by 15%, the break even point increases and profits decrease and vice versa.